Penerapan Alat Bukti Kesaksian Testimonium De Auditu Dalam Perkara Permohonan Pengesahan Nikah Di Samarinda - Latifatul Fajriyyah (SAMAWA, 2022)
The witness testimony that was justified in civil proceedings was someone who has directly involved in an event based on clause 171 verse (1) and (2) HIR, 308 RBg, and 1907 Civil Code. Meanwhile, the witnesses who are presented outside of these provisions are the testimonium de auditu. In its application there is a difference between the Religious Courts (PA) in Decision Number 1003/Pdt.G/2017/PA.Smd and the Religious High Court (PTA) in Verdict Number 14/Pdt.G/2018/PTA.Smd. These differences lead to inconsistencies in the application of the law at the evidentiary stage. This research is a normative study that uses a case, statutory and conceptual approach. The results of this study are, the application of evidence de auditu in the case of a marriage ratification application was accepted as evidence by Judge PA Samarinda because there was an agreement with other evidence. Meanwhile, the Samarinda PTA Judge rejected the de auditu witness as evidence on the grounds that the de auditu witness could not be applied in a disputed case and the legal principles of proof in the application of the law by the PA and PTA Samarinda had not been fulfilled completely. This is because in legal considerations by the PA and PTA Samarinda Judges, they did not provide clear and sufficient legal arguments regarding the acceptance or rejection of the de auditu witness.